Constructing a human complex type N-linked glycosylation pathway in Kluyveromyces marxianus - Lee, Ming-Hsuan; Hsu, Tsui-Ling; Lin, Jinn-Jy; Lin, Yu-Ju; Kao, Yi-Ying; Chang, Jui-Jen; Li, Wen-Hsiung (PloS one, 2020)
Glycosylation can affect various protein properties such as stability, biological activity, and immunogenicity. To produce human therapeutic proteins, a host that can produce glycoproteins with correct glycan structures is required. Microbial expression systems offer economical, rapid and serum-free production and are more amenable to genetic manipulation. In this study, we developed a protocol for CRISPR/Cas9 multiple gene knockouts and knockins in Kluyveromyces marxianus, a probiotic yeast with a rapid growth rate. As hyper-mannosylation is a common problem in yeast, we first knocked out the α-1,3-mannosyltransferase (ALG3) and α-1,6-mannosyltransferase (OCH1) genes to reduce mannosylation. We also knocked out the subunit of the telomeric Ku domain (KU70) to increase the homologous recombination efficiency of K. marxianus. In addition, we knocked in the MdsI (α-1,2-mannosidase) gene to reduce mannosylation and the GnTI (β-1,2-N-acetylglucosaminyltransferase I) and GnTII genes to produce human N-glycan structures. We finally obtained two strains that can produce low amounts of the core N-glycan Man3GlcNAc2 and the human complex N-glycan Man3GlcNAc4, where Man is mannose and GlcNAc is N-acetylglucosamine. This study lays a cornerstone of glycosylation engineering in K. marxianus toward producing human glycoproteins.